Collaborative approach to Optimise MEdication use for Older people in Nursing homes (COME-ON): study protocol of a cluster controlled trial. (December 2015) - Anrys, Pauline; Strauven, Goedele; Boland, Benoit; Dalleur, Olivia; Declercq, Anja; Degryse, Jean-Marie; De Lepeleire, Jan; Henrard, Séverine; Lacour, Valérie; Simoens, Steven; Speybroeck, Niko; Vanhaecht, Kris; et al.
Abstract Background Ageing has become a worldwide reality and presents new challenges for the health-care system. Research has shown that potentially inappropriate prescribing, both potentially inappropriate medications and potentially prescribing omissions, is highly prevalent in older people, especially in the nursing home setting. The presence of potentially inappropriate medications/potentially prescribing omissions is associated with adverse drug events, hospitalisations, mortality and health-care costs. The Collaborative approach to Optimise MEdication use for Older people in Nursing homes (COME-ON) study aims to evaluate the effect of a complex, multifaceted intervention, including interdisciplinary case conferences, on the appropriateness of prescribing of medicines for older people in Belgian nursing homes. Methods/design A multicentre cluster-controlled trial is set up in 63 Belgian nursing homes (30 intervention; 33 control). In each of these nursing homes, 35 residents (≥65 years) are selected for participation. The complex, multifaceted intervention comprises (i) health-care professional education and training, (ii) local concertation (discussion on the appropriate use of at least one medication class at the level of the nursing home) and (iii) repeated interdisciplinary case conferences between general practitioner, nurse and pharmacist to perform medication review for each included nursing home resident. The control group works as usual. The study period lasts 15 months. The primary outcome measures relate to the appropriateness of prescribing and are defined as (1) among residents who had at least one potentially inappropriate medication/potentially prescribing omission at baseline, the proportion of them for whom there is a decrease of at least one of these potentially inappropriate medications/potentially prescribing omissions at the end of study, and (2) among all residents, the proportion of them for whom at least one new potentially inappropriate medication/potentially prescribing omission is present at the end of the study, compared to baseline. The secondary outcome measures include individual components of appropriateness of prescribing, medication use, outcomes of the case conferences, clinical outcomes and costs. A process evaluation (focusing on implementation, causal mechanisms and contextual factors) will be conducted alongside the study. Discussion The COME-ON study will contribute to a growing body of knowledge concerning the effect of complex interventions on the use of medicines in the nursing home setting, and on factors influencing their effect. The results will inform policymakers on strategies to implement in the near future. Trial registration Current Controlled TrialsISRCTN66138978